Autologous and homologous skin grafts treated with platelet-rich plasma (PRP): experimental study in rabbits - Kemper, Bernardo [UNESP]; Brandao, Claudia V. S. [UNESP]; Rossetto, Victor J. V. [UNESP]; Gushiken, Lucas F. S. [UNESP]; Padovani, Carlos R. [UNESP]; Pellizzon, Claudia H. [UNESP] (Revista Pesquisa Veterinaria Brasileira, 2018)
The aim of the present study was to compare tissue repair of skin defects in rabbits submitted to autologous and homologous grafts treated or not with platelet-rich plasma (PRP). We selected nine rabbits and constituted four groups, designated as G1, in which were performed autologous graft treated with PRP; G2, autologous graft only; G3, homologous graft treated with PRP; and G4, homologous graft only. Macroscopic and histomorphometric evaluation was realized. The histomorphometric evaluation was performed by Hematoxylin/Eosin and Masson's Trichrome staining with quantification of collagen fibers, macrophages, fibroblasts and vessels. The autologous graft treated with PRP showed positive influence on the early stage of the tissue repair process at the macroscopic evaluation, characterized by rosy color and cosmetic appearance. At the histomorphometric evaluation, there was no statistical difference in the number of macrophages and fibroblasts between the treated grafts or not with the PRP, as well as the quantification of vessels and collagen fibers. It can be concluded that PRP promotes a positive influence on the initial phase or take of the graft.
Keywords: Skin grafts; platelet-rich plasma; rabbits; skin transplantation; wound healing; tissue repair; allografts; autografts; surgery